(untitled) (Research, Society and Development, 2020)
Handroanthus chrysotrichus is a tree of the Bignoniaceae family known as golden trumpet that is distributed throughout Northeast, Southeast and South Brazil. Its flowers, stem and bark are used for medicinal purposes in the treatment of cardiovascular and immune system diseases. This study aims to evaluate the phytochemical profile, biological activity spectrum, antioxidant capacity and toxicological potential of H. chrysotrichus stem bark extract. Hydroethanolic extract was obtained by percolation and lyophilized. Compounds present in the extract were analyzed by colorimetric methods and by GC-MS. Evaluation of the biological activity spectrum was performed in silico. Antioxidant power was determined by investigation of total antioxidant capacity, iron chelating capacity, DPPH• and ABTS•+ assays, and deoxyribose degradation test. The ability to inhibit Fe+ induced lipoperoxidation was evaluated in mouse brains and livers. Nauplii of Artemia salina were used to evaluate the median lethal dose. Toxicity was assessed by computer simulation, and in vitro in human lymphocytes. As a result, colorimetric methods suggest high levels of polyphenols and GC-MS data indicated the occurrence of α-curcumene, β-bisabolene, 4- (4-methylphenyl) pentanal, pentanoic acid and isoamyl acetate. Computer simulations have pointed biological activities that are in accordance with their traditional use. The H. chrysotrichus stem bark extract exhibited antioxidant activity in several assays and was effective in protecting mouse brains and livers from Fe+ induced lipoperoxidation. H. chrysotrichus stem bark extract showed medium toxicity in A. salina with potential presence of bioactive compounds. In general, the compounds showed low probability of toxicity in silico predictions. There was no cytotoxicity and genotoxicity in human lymphocyte evaluation. The results indicate that H. chrysotrichus stem bark extract has compounds with biological activity spectrum and low toxicological potential. It also shows antioxidant capacity and protective action against lipid peroxidation. The data presented support the medicinal use of golden trumpet and point to it as a promising extract for in vivo evaluations.